2018
DOI: 10.3389/fmars.2018.00184
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future: Performance of Two Bivalve Species Under Changing Environmental Conditions

Abstract: Globally, the production of marine bivalves has been steadily increasing over the past several decades. As the effects of human population growth are magnified, bivalves help provide food security as a source of inexpensive protein. However, as climate change alters sea surface temperatures (SST), the physiology, and thus the survival, growth, and distribution of bivalves are being altered. Challenges with managing bivalves may become more pronounced, as the uncertainty associated with climate change makes it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 86 publications
(124 reference statements)
0
33
0
1
Order By: Relevance
“…The region has the world's fastest sea level rise, approximately 3-4 times faster than the world average [99], drowning saltmarshes [100] and posing a serious threat to the very existence of intertidal mudflats [101]. As mussel beds collapse in the Gulf of Maine and elsewhere due to climate change [16][17][18][19][20][21] and predation by the invasive green crab, Carcinus maenas [22][23][24][25], at what density and spatial arrangement of individuals will we decide they have ceased to exist as ecosystem engineers? Is it possible that the formerly robust mussel bed at Carrying Place Cove has been depleted of mussels to such a degree that it can no longer even be called a mussel bed?…”
Section: Space and Time In Collapsed Mussel Bedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The region has the world's fastest sea level rise, approximately 3-4 times faster than the world average [99], drowning saltmarshes [100] and posing a serious threat to the very existence of intertidal mudflats [101]. As mussel beds collapse in the Gulf of Maine and elsewhere due to climate change [16][17][18][19][20][21] and predation by the invasive green crab, Carcinus maenas [22][23][24][25], at what density and spatial arrangement of individuals will we decide they have ceased to exist as ecosystem engineers? Is it possible that the formerly robust mussel bed at Carrying Place Cove has been depleted of mussels to such a degree that it can no longer even be called a mussel bed?…”
Section: Space and Time In Collapsed Mussel Bedsmentioning
confidence: 99%
“…Mussel beds can experience dramatic short-and long-term changes in abundance [11][12][13][14][15]. They appear to be declining in the Gulf of Maine, apparently due to climate change [16][17][18][19][20][21] and predation by the invasive green crab, Carcinus maenas [22][23][24][25]. When mussels die, they leave behind large expanses of non-living biogenic material in the form of shell hash [3,4,26] ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaccumulation of fish viruses in invertebrate tissues poses a serious threat for the susceptible species, which has been well documented by monitoring the rate and efficiency of this phenomenon (Arzul, Corbeil, Morga, & Renault, 2017). The case of bioaccumulation of virus particles by filter feeders becomes much more complicated in the context of climate change that directly affects abiotic factors (mainly temperature) of the aquatic environment and, in consequence, imposes effects on the invertebrate physiology (Steeves, Filgueira, Guyondet, Chassé, & Comeau, 2018). The only results concerning the CyHV‐3 DNA presence in the invertebrate tissues have been described for the swan mussel ( Anodonta cygnea ) and scud ( Gammarus pulex ) in Poland (Kiełpiński et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, Meyers (1984, and references therein) indicated that for infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV), the efficiency of particle bioaccumulation in the tissues of invertebrates depends largely on the physical characteristics of the agent and the physico‐chemical properties of the ambient water. The case of bioaccumulation of virus particles by filter feeders becomes much more complicated in the context of climate change, which directly affects abiotic factors (mainly temperature) of the aquatic environment and, in consequence, imposes effects on the invertebrate physiology (Steeves et al., 2018). In our opinion, further studies should also consider whether native or alien invertebrate species are able to effectively remove CyHV‐3 and other pathogens from the water column via degradation and naturally mitigate the risk of disease to aquaculture, wildlife and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Environmentally, for example, while salmon aquaculture can produce significant pollution and escapement problems [7][8], not all types of marine aquaculture create those problems. In the United States, for example, about two-thirds of marine aquaculture production by value consists of clams, mussels, and oysters [2], and these filter-feeding mollusks often improve water quality, especially because most bivalve aquaculture does not require feeding [9][10]. Similarly, escape into the wild is not an issue when aquaculture operations use unmodified native species.…”
mentioning
confidence: 99%